Market failure vs. system failure as a rationale for EU regional policy? A critique from an evolutionary economic perspective - Peter Schmidt (European Regional Science Association (ERSA), 2015)
This paper reconsiders the economic explanation of EU regional policy from an evolution- ary perspective. It contrasts the neoclassical equilibrium notions of market and government failure with the prevalent evolutionary neo-Schumpeterian and Austrian-Hayekian percep- tions. Based on this comparison the paper criticises that neoclassical failure reasoning still prevails in non-equilibrium evolutionary economics when regional policy issues are exam- ined. This is more than surprising since proponents of evolutionary economics usually view their approach as incompatible with its neoclassical counterpart. In addition, it is shown that this ?fallacy of failure thinking? even finds its continuation in the alternative concept of ?system failure? with which some evolutionary economists try to explain and legitimate regional policy interventions in local, regional or national innovation systems. The paper argues that in order to prevent the fruitful and more realistic evolutionary approach from undermining its own criticism of neoclassical economics and to create a consistent as well as objective evolutionary policy framework it is necessary to eliminate the equilibrium spirit from it. Finally, the paper delivers an alternative evolutionary explanation of EU regional policy which is able to overcome the theory-immanent contradiction of the hitherto evolu- tionary view on this subject. Building on the preceding remarks, policy implications for EU regional policy from a ?proper? evolutionary perspective are deduced.
Keywords: B52; B53; F15; H53; O20; R10; 330; market failure; system failure; EU regional policy; evolutionary economics